Beyond Religious Borders: Interaction and Intellectual Exchange in the Medieval Islamic World - Freidenreich, David M.; Goldstein, Miriam (Jewish Culture and Contexts, 2012)
Biographical note: David M. Freidenreich teaches Jewish studies at Colby College. Miriam Goldstein is Lecturer in the Department of Arabic Language and Literature at the Hebrew University of Jerusalem.